Inorganic component of saliva during fasting and after fast break - Yusrini Selviani; Nurul W. Mas’ud; Arsmin NI. Fitri; Atikah B. Ferry; Rini F. Lestari; Rasmidar Samad (Journal of Dentomaxillofacial Science, 2016)
Oral health is closely related to salivary components. Saliva consists of water, inorganic and organic materials. Fasting changes one’s meal and drinking time that in turn can affect the environment in oral cavity, including inorganic componenet of saliva. The purpose of this study is to determine the inorganic component of saliva during fasting and after fast break. The study is an observational analytic (longitudinal/follow-up study) conducted in Hasanuddin University dental hospital in July 2015. The sampling method is purposive sampling with the entire population of Dental Public Health section students, who are 35 people with 16 research subjects who fullfill the criteria of the study. Samples were tested in the laboratory using Atomic Absorption Spectrophotometer (AAS) in part per million (ppm) units. The data is analysed by paired t-test with SPSS version 17.0. The result shows that concentration of inorganic components (calcium, phosphate and potassium) in the saliva decreased significantly after fast break (p<0.05). Sodium shows decreased insignificantly after fast break (p=0.190) and magnesium increased insignificantly after break fasting (p=0.615). The concentration of calcium, phosphate, potassium except sodium decreased significantly after fast break, whereas the concentrations of magnesium were not significantly increased after fast break.